2021
DOI: 10.1080/08164622.2021.1959265
|View full text |Cite
|
Sign up to set email alerts
|

How practitioners say they answer the questions of patients about ultraviolet protection

Abstract: Patients should be able to rely on optometrists and optical dispensers to provide evidence-based answers to their questions on eye protection, including against ultraviolet radiation. Surveys indicate that there is public concern about the need for protection against ultraviolet radiation, particularly in sunlight. This investigation aimed to evaluate the quality of information provided by practitioners in response to typical questions to which they might reasonably be expected to have ready answers. A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Studies have shown that the adverse physiological reactions caused by stroboscopic flicker include distraction and vision loss [ 9 ]. With the popularization of photobiological effects theory [ 10 ], the role of nonvisual effects in the evaluation of lighting environments has gained more attention. Zhonggui-Yin et al [ 11 ] conducted a clinical analysis of 503 cases of asthenopia and found that the lighting environment had a greater impact on asthenopia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the adverse physiological reactions caused by stroboscopic flicker include distraction and vision loss [ 9 ]. With the popularization of photobiological effects theory [ 10 ], the role of nonvisual effects in the evaluation of lighting environments has gained more attention. Zhonggui-Yin et al [ 11 ] conducted a clinical analysis of 503 cases of asthenopia and found that the lighting environment had a greater impact on asthenopia.…”
Section: Introductionmentioning
confidence: 99%